Fracturing and Groundwater Productivity Linkages in the Koumfab Watershed in Northern Togo - P.E., Katansao; M.E., Gnazou; M.S., Tairo; M.D.T., Gnazou; V., Ljiljana (European Scientific Journal, ESJ, 2023)
The Koumfab watershed, located in the Dapaong region of northern Togo, overlies the sandstone-pelite formations of the lower megasequence of the Volta Basin and the granito-migmatitic bedrock of the south-eastern edge of the West African Craton. All of these Precambrian formations have a dense network of lineaments or fractures, giving them the characteristics of discontinuous and highly exploited aquifers. The lineament map of the Koumfab watershed, obtained from aerial photographs and the digital terrain model, identifies three main families of fractures running N-S to NE-SW (N0° to N40°), NE-SW to ESE-WNW (N60° to N110°) and ESE-WNW to SE-NW (N120° to N180°). Analysis of the correlation between lineaments and borehole flow rates has enabled us to identify areas with high storage potential. This potential is mainly controlled by lithological and lineament parameters. Boreholes drilled along kilometre-long lineaments underlain by crystalline and sandstone formations are more productive, with generally high flow rates (Q > 5m3/h). The basement formations found throughout the Koumfab catchment are major reservoirs with hydrogeological potential that are already in great demand.